2003
DOI: 10.1042/bj20021301
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of alphav/beta3 integrin via misrouting to lysosomes by overexpression of a beta3Lamp1 fusion protein

Abstract: We present a general strategy for the dominant negative reduction in the levels of type-1 membrane-bound heterodimeric proteins within the secretory pathway through fusion of the soluble ectodomain of one of the partners to the transmembrane-cytosolic tail of the lysosomal protein Lamp1. Thus, in human embryonic kidney (HEK)-293 cells, overexpression of an integrin beta 3Lamp1 chimera resulted in a drastic reduction of its endogenous partner, the integrin alpha v subunit. The mechanism involves the formation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Instead, the major factor affecting what a-b combinations are present on the cell surface seems to be the cell's integrin subunit expression profile, the types, and relative abundance. For example, manipulating the amount of an a subunit (e.g., by overexpression) affects the a-b combinations expressed by a cell [57][58][59][60][61][62]. In many cell types (including eggs [17,19]), ITGB1 is a highly abundant b subunit, favoring ITGB1 dimerization with the available a subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the major factor affecting what a-b combinations are present on the cell surface seems to be the cell's integrin subunit expression profile, the types, and relative abundance. For example, manipulating the amount of an a subunit (e.g., by overexpression) affects the a-b combinations expressed by a cell [57][58][59][60][61][62]. In many cell types (including eggs [17,19]), ITGB1 is a highly abundant b subunit, favoring ITGB1 dimerization with the available a subunits.…”
Section: Discussionmentioning
confidence: 99%
“…The next question was whether TIMP-2 could recruit PC5A to the cell surface, possibly in proximity to a protein that binds the complex TIMP-2/PC5A. Accordingly, we used a cell-based missorting approach (Conesa et al, 2003) as well as coimmunoprecipitation and immunocytochemical colocalization techniques. The data demonstrated that the C-terminal segment of TIMP-2 binds the CRD of PC5A (Figure 8) and that cell surface immobilized TIMP-2 is required for the plasma membrane colocalization of PC5A with TIMP-2 (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis, we used a cellular missorting technique previously applied to ␤3-integrin (Conesa et al, 2003), whereby the C termini of soluble TIMP-2 or the ectodomain of MT1-MMP were fused to a lysosomal/endosomal targeting sequence consisting of the Lamp1 transmembrane-cytosolic tail, herein named TIMP-2-LP ( Figure 3A) and MT1-MMP-LP. According to this dominant negative technique, partners of TIMP-2 or MT1-MMP would be expected to cycle to the cell surface and be dragged to the endosomal/lysosomal compartments for degradation (Conesa et al, 2003). The data revealed that both MT1-MMP and MT1-MMP-LP do not significantly affect the level of C-terminal cleavage of PC5A or the secretion of its CRD (our unpublished data), suggesting that PC5 may not bind robustly MT1-MMP.…”
Section: Timp-2 Interacts With Pc5a Via the Crdmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibody to LRP1 (C-terminal Ab377) was a generous gift of J. Herz (University of Texas, Dallas). Stable transfectants of empty bicistronic pIRES2-EGFP vector, V5-tagged wild type NARC-1 and its mutants H226A, S127R, and D374Y were obtained in the human hepatocyte-derived cell line HepG2 following G418 selection and FACS purification of fluorescent cells (25).…”
Section: Methodsmentioning
confidence: 99%